2013
DOI: 10.1186/1471-2164-14-848
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of blood lipid traits by integrating genome-wide association study and gene expression profiling in a porcine model

Abstract: BackgroundSerum concentrations of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) are highly heritable traits that are used clinically to evaluate risk for cardiovascular disease in humans. In this study, we applied a genome-wide association study (GWAS) in 1,075 pigs from two populations and gene expression studies on 497 liver samples to dissect the genetic basis of serum lipids in a pig model.ResultsWe totally identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…As previously said, one of the most promising candidate genes is apolipoprotein B ( APOB , located at SSC3 125.2 Mb), which has been identified in our study as well as in the GWAS performed by Chen et al [9]. Apolipoprotein B is essential for the correct assembly of chylomicrons and the synthesis of very low density lipoproteins (VLDL), that transport TRIG from the intestine to other body tissues [35].…”
Section: Discussionmentioning
confidence: 62%
“…As previously said, one of the most promising candidate genes is apolipoprotein B ( APOB , located at SSC3 125.2 Mb), which has been identified in our study as well as in the GWAS performed by Chen et al [9]. Apolipoprotein B is essential for the correct assembly of chylomicrons and the synthesis of very low density lipoproteins (VLDL), that transport TRIG from the intestine to other body tissues [35].…”
Section: Discussionmentioning
confidence: 62%
“…In our GWAS (Chen et al . ), this QTL was evidenced in this F 2 population, but it achieved only a chromosomal‐wide significance level. Furthermore, in a Sutai population, we found that this QTL showed the most predominant effect on LDL‐C and TC in a GWAS (Chen et al .…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, in a Sutai population, we found that this QTL showed the most predominant effect on LDL‐C and TC in a GWAS (Chen et al . ). We also investigated the associations of whole‐genome gene expressions in liver with serum lipids.…”
Section: Introductionmentioning
confidence: 97%
“…mcw.edu/) and mice (http://www.informatics.jax.org/), but few studies have investigated QTL for serum lipids in pigs. Recently, a number of QTLs have been mapped for porcine blood lipids using whole genome-linkage analysis (Gallardo et al 2008;Uddin et al 2011) and the genome-wide association approach (Chen et al 2013). To date, 43 QTL for total cholesterol (TC), 21 for high-density lipoprotein cholesterol (HDL-C), 68 for low-density lipoprotein cholesterol (LDL-C), 22 for HDL-C/LDL-C and 25 for triglycerides (TG) have been reported in the pig QTL database (http:// www.animalgenome.org/cgi-bin/QTLdb/SS/index).…”
mentioning
confidence: 99%
“…The samples were processed to measure serum TC (TC 45 , TC 300 ), LDL-C (LDL-C 45, LDL-C 300 ), HDL-C (HDL-C 45 , HDL-C 300 ) and TG (TG 45 , TG 300 ) concentrations as described by Chen et al (2013). Blood collection took place between 8:00 and 10:00 a.m. after an overnight fast (approximately 12 h).…”
mentioning
confidence: 99%